RNA Extraction from Endoscopic Ultrasound-Acquired Tissue of Pancreatic Cancer Is Feasible and Allows Investigation of Molecular Features - Livia Archibugi; Veronica Ruta; Valentina Panzeri; Miriam Redegalli; Sabrina Gloria Giulia Testoni; Maria Chiara Petrone; Gemma Rossi; Massimo Falconi; Michele Reni; Claudio Doglioni; Claudio Sette; Paolo Giorgio Arcidiacono; et al. (Cells, 2020)
Transcriptome analyses allow the distinguishing of pancreatic ductal adenocarcinoma (PDAC) subtypes, exhibiting different prognoses and chemotherapy responses. However, RNA extraction from pancreatic tissue is cumbersome and has been performed mainly from surgical samples, which are representative of < 20% of cases. The majority of PDAC patients undergo endoscopic ultrasound (EUS)-guided tissue acquisition (EUS-TA), but RNA has been rarely extracted from EUS-TA with scanty results. Herein, we aimed to determine the best conditions for RNA extraction and analysis from PDAC EUS-TA samples in order to carry out molecular analyses. PDAC cases underwent diagnostic EUS-TA, with needles being a 25G fine needle aspiration (FNA) in all patients and then either a 20G lateral core-trap fine needle biopsy (FNB) or a 25G Franseen FNB; the conservation methods were either snap freezing, RNALater or Trizol. RNA concentration and quality (RNA integrity index; RIN) were analyzed and a panel of genes was investigated for tissue contamination and markers of molecular subtype and aggressivity through qRT-PCR. Seventy-four samples from 37 patients were collected. The median RNA concentration was significantly higher in Trizol samples (10.33 ng/uL) compared with snap frozen (0.64 ng/uL; p < 0.0001) and RNALater (0.19 ng/uL; p < 0.0001). The RIN was similar between Trizol (5.15) and snap frozen samples (5.85), while for both methods it was higher compared with RNALater (2.7). Among the needles, no substantial difference was seen in terms of RNA concentration and quality. qRT-PCR analyses revealed that samples from all needles were suitable for the detection of PDAC subtype markers (GATA6 and ZEB1) and splice variants associated with mutational status (GAP17) as well as for the detection of contaminating tissue around PDAC cells. This is the first study that specifically investigates the best methodology for RNA extraction from EUS-TA. A higher amount of good quality RNA is obtainable with conservation in Trizol with a clear superiority of neither FNA nor FNB needles. RNA samples from EUS-TA are suitable for transcriptome analysis including the investigation of molecular subtype and splice variants expression.